Pengembangan Pembelajaran Kearsipan Melalui Pelatihan Electronic Filing System (EFS) dengan Program IWSM di Sekolah Menengah Kejuruan (SMK) - Ma'mun Sutisna; Titin Suhaeni; Maya Setiawardani; Mukaram Mukaram; Sri Raharso; Ermina Tiorida; Harmon Harmon (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
The review of Vocational High School Curriculum 2013 in 2017 brought significant changes to the learning process at the Vocational High School level, it is a change of the expertise competency name that was originally an Office Administration into Automation and Office Governance (AOG). There is a subject in the AOG expertise competency, Archive, which is included in the Basic Subject Group of Expertise Program (C2). In the syllabus of archival subjects, which were originally only manual archiving not only containing manual archive management but also the application of electronic archive management. According to the new topic, teachers do not have competence in the field yet, therefore the training is needed. The purpose of this training is to improve teacher’s competence in the field of Electronic Filing System (EFS) by using the Scan Manager program. This training lasts for five days on the campus, and one week on the field under the guidance of a lecturer at the Business Administration program, Politeknik Negeri Bandung. The result of the training showed that the attendance of participants in the training was 95%, the mastery of training material before and after was 97.6%, and all participants as many as 16 people were declared competent, 2 people were quite competent and entitled to get the certificate. Electronic Filing System (EFS) competency improvement training to maximize the teaching of e-filing with the Scan Manager program in vocational high schools, can be done well and reach suggestions in accordance with the proposals.